Seminal Attributes and their Correlations in Surti Bucks - Kumar, David; Khasatiya, Chandubhai T.; Chaudhari, Naresh F.; Modi, Lalit C.; Singh, Virendra K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present work was carried out to study seminal attributes of fresh ejaculates of Surti bucks and their correlations. Four healthy mature  Surti bucks (aged >2 years) were selected. Fresh semen was collected twice a week for 8 weeks from each buck, i.e., 64 ejaculates (16 from  each buck). Fresh semen was analyzed for color, pH, volume, density, mass activity/motility, sperm concentration/mL, and total sperm  count/ejaculate. Fresh semen was pale yellow in color and its pH ranged from 6.7 to 6.9. The overall mean values of semen volume,  density, mass activity/motility, sperm concentration, and total sperm count recorded were 0.47 ± 0.02 mL, 3.31 ± 0.08, 3.39 ± 0.08,  3932.81 ± 43.25 million/mL, and 1839.69±72.75 million, respectively. The ejaculate volume and sperm concentration/mL only varied  significantly among bucks. Ejaculate volume was negatively correlated with sperm concentration/mL (r = -0.302), and positively with  total sperm output/ejaculate (r = 0.961) and density score (r = 0.604), while the latter two were significantly interrelated (r = 0.605). The  study established the normal values of fresh semen quality parameters of Surti bucks and their interrelations.
Keywords: Correlations; Seminal Attributes; Surti bucks